Chronic hepatitis C: future treatment - Wendt A; Adhoute X; Castellani P; Oules V; Ansaldi C; Benali S; Bourlière M (Dove Medical Press, 2014)
Astrid Wendt, Xavier Adhoute, Paul Castellani, Valerie Oules, Christelle Ansaldi, Souad Benali, Marc BourlièreDepartment of Hepato-Gastroenterology, Hôpital Saint-Joseph, Marseille, FranceAbstract: The launch of first-generation protease inhibitors (PIs) is a major step forward in HCV treatment. However, the major advance is up to now restricted to genotype 1 (GT-1) patients. The development of second-wave and second-generation PIs yields higher antiviral potency through plurigenotypic activity, more convenient daily administration, fewer side effects and, for the second-generation PIs, potential activity against resistance-associated variants. NS5B inhibitors include nucleoside/nucleotide inhibitors (NIs) and non-nucleotide inhibitors (NNIs). NIs have high efficacy across all genotypes. Sofosbuvir has highly potent antiviral activity across all genotypes in association with pegylated interferon and ribavirin (PR), thus allowing shortened treatment duration. NS5A inhibitors (NS5A.I) have highly potent antiviral activity. It has recently been shown for the first time that NS5A.I in combination with protease inhibitors can cure GT-1b null responders in an interferon-free regimen. Besides, several studies demonstrate that interferon (IFN)-free regimens with direct-acting antiviral agent combinations are able to cure a large number of either naïve or treatment-experienced GT-1 patients. Moreover, quadruple regimen with PR is able to cure almost all GT-1 null responders. The development of pan-genotypic direct-acting antiviral agents (NIs or NS5A.I) allows new combinations with or without PR that increase the rate of sustained virological response for all patients, even for those with cirrhosis and independently of the genotype. Therefore, the near future of HCV treatment looks promising. The purpose of this article is to provide an overview of the clinical results recently reported for HCV treatment.Keywords: SVR, direct antiviral agents, host-targeting agents, interferon-free regimen, pangenotypic activity, cirrhosis